Penerapan Sanksi Terhadap Pelaku Pelanggaran Undang Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan - Saryana, Saryana (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
To reduce the number of traffic accidents which are felt to be very high, it is directed at a comprehensive response that includes efforts to develop,prevent, regulate and enforce the law.Legal certainty must be upheld, but justice and expediency are far more important to implement.The issues to be discussed are : (1) What are the sanctions for violations of Law Number 22 of 2009? and(2) How are the sanctions applied to perpetrators of violations of Law Number 22 of 2009?This writing uses a normative and empirical juridical approach, using primary data sources and secondary data sources.From the results of the writing it can be concluded that(1) sanctions for violations of Law Number 22 of 2009 are differentiated into sanctions for criminal acts of violation and sanctions for criminal acts, each of which has criminal provisions or fines, the types of crimes and the severity of crimes are determined in various ways, and(2) the application of sanctions against perpetrators of violations of Law Number 22 of 2009 concerning road traffic and transportation cannot be applied by law enforcement officials as formulated by Law Number 22 of 2009, this is caused by the existence of several existing policy factors, including( a) the existence of the police who allow reconciliation of traffic accident crimes on the highway, (b) the existence of reconciliation carried out by the perpetrators of traffic accident crimes, (c) the provision of compensation and compensation as a form of peace from the perpetrators of traffic accident crimes cross. Keywords: application of sanctions; perpetrators of law violations; road transport traffic